Gender Bias: the Distribution of Power and Social Roles in the Minangkabau Society - Melly Tria Utari; Syahri Ramadhan (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
Gender bias often emerges from unequal role distribution between women and men, including in societies that are normatively regarded as gender inclusive. The Minangkabau community, widely recognized for its matrilineal kinship system, is frequently assumed to privilege women; however, empirical realities indicate persistent gender asymmetries in power and authority. This study examines how gender bias manifests within Minangkabau customary structures, particularly in relation to social roles, authority, and political participation. Employing a qualitative research design with an ethnomethodological approach, data were collected through in-depth interviews, participant observation, and critical analysis of relevant literature. Informants included traditional leaders, Minangkabau women, and authoritative written sources on customary norms and social organization in West Sumatra. The findings reveal three dominant patterns of gender bias: women exercise authority over lineage and inheritance but remain excluded from formal political power; women, symbolically revered as Bundo Kanduang and custodians of the Rumah Gadang, hold limited substantive authority; and a dualistic role structure persists within domestic life, reinforcing unequal gender expectations. The study argues that matrilineality does not automatically ensure gender equality and underscores the need for critical engagement with customary systems to promote women’s substantive, rather than symbolic, participation in socio-political spaces.